BARRIERS TO PARTICIPATION IN TOURISM FOR PEOPLE WITH DISABILITIES: POLICY AND PRACTICE PERSPECTIVES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Inclusive tourism is an increasing worldwide priority, focusing on guaranteeing equitable access for all individuals, including those with impairments. Notwithstanding regulatory initiatives and lobbying for universal design, certain obstacles continue to impede the complete engagement of handicapped persons in tourist experiences. This essay analyzes these obstacles from both policy and practical perspectives, emphasizing physical, economic, attitudinal, and informational limitations. It also examines international and national policy frameworks, including the UN Convention on the Rights of Persons with Disabilities (CRPD), and evaluates the effectiveness of their implementation in tourism. The essay analyzes case studies and stakeholder activities to identify best practices and provide methods for developing more inclusive and